The risk of postoperative complications and functional impairment after multimodality treatment for limb and trunk wall soft-tissue sarcoma: Long term results from a monocentric series. Issue 6 (June 2017) - Stoeckle, E.; Michot, A.; Rigal, L.; Babre, F.; Sargos, P.; Henriques de Figueiredo, B.; Brouste, V.; Italiano, A.; Toulmonde, M.; Le Loarer, F.; Kind, M.
Abstract: Background and objectives: Conservative surgery for soft-tissue sarcoma (STS) within multimodality treatment attempts to reconcile two contradictory requirements: assuring a good oncological outcome through a wide resection and preserving the function. The aim of our study is to verify whether our conservative approach to STS met these objectives. Methods: A retrospective database analysis was performed in adults with primary limb or trunk wall STS operated in a single center from 1989 to 2012. Predictive factors for postoperative complications and functional impairment were tested in a multivariate analysis. Results: 728 patients were operated (resection R0: 68%). Neoadjuvant chemotherapy (NAC) was given to 28%, postoperative radiotherapy to 70% of patients. Median follow-up was 103 months. At five years, overall survival was 80% and local recurrences 11%. Major postoperative complications occurred in 8% and functional impairment in 13% of the patients. Independent predictive factors for postoperative complications were American Society of Anesthesiologist classes 2 and 3 (OR: 2.3, CI: 1.2–4.5 and 4.0 CI: 1.7–9.3), tumor size >80 mm (OR: 2.5, CI: 1.3–4.9), tumor site (trunk wall/lower limb, OR: 4.1, CI: 1.3–13.6) and multifocal/multicompartmental spread (OR: 2, CI: 1.1–3.6). Independent predictive factors for function impairment were postoperative complications (OR: 5.3, CI: 2.8–10.1), NAC (OR: 3.6, CI: 2.2–5.8), and bone or neurovascular involvement (OR 3.3, CI 2.0–5.3), whereas Early Rehabilitation after Surgery (ERAS) improved outcome (OR: 0.5, CI: 0.3–0.9). Conclusion: Postoperative complications induced functional impairment. They may be reduced by acting on comorbidity factors and careful tumor evaluation prior to surgery. Furthermore, ERAS measures improved function.